Telehealth and cardiometabolic-based chronic disease: optimizing preventive care in forcibly displaced migrant populations - Ramfis Nieto-Martínez; Diana De Oliveira-Gomes; Juan P. Gonzalez-Rivas; Tala Al-Rousan; Jeffrey I. Mechanick; Goodarz Danaei; The Migrants Health Lown Scholar Program Team (Journal of Health, Population and Nutrition, 2023)
Abstract The number of migrants, which includes forcibly displaced refugees, asylum seekers, and undocumented persons, is increasing worldwide. The global migrant population is heterogeneous in terms of medical conditions and vulnerability resulting from non-optimal metabolic risk factors in the country of origin (e.g., abnormal adiposity, dysglycemia, hypertension, and dyslipidemia), adverse travel conditions and the resulting stress, poverty, and anxiety, and varying effects of acculturation and access to healthcare services in the country of destination. Therefore, many of these migrants develop a high risk for cardiovascular disease and face the significant challenge of overcoming economic and health system barriers to accessing quality healthcare. In the host countries, healthcare professionals experience difficulties providing care to migrants, including cultural and language barriers, and limited institutional capacities, especially for those with non-legal status. Telehealth is an effective strategy to mitigate cardiometabolic risk factors primarily by promoting healthy lifestyle changes and pharmacotherapeutic adjustments. In this descriptive review, the role of telehealth in preventing the development and progression of cardiometabolic disease is explored with a specific focus on type 2 diabetes and hypertension in forcibly displaced migrants. Until now, there are few studies showing that culturally adapted telehealth services can decrease the burden of T2D and HTN. Despite study limitations, telehealth outcomes are comparable to those of traditional health care with the advantages of having better accessibility for difficult-to-reach populations such as forcibly displaced migrants and reducing healthcare associated costs. More prospective studies implementing telemedicine strategies to treat cardiometabolic disease burden in migrant populations are needed.